Occurrences and distribution of Arsenic in waterways at the Pejiru Gold Prospect area in Bau District, Kuching, Sarawak - Nathan, Achuk (Universiti Malaysia Sarawak, (UNIMAS), 2013)
(In Bau district arsenic is associated with numerous gold deposits. A study on the occurrence of arsenic at one of the gold deposit at Pejiru was conducted to determine the occurrences and distribution of arsenic in the various water waterways in the area. Samples of water and sediment were collected from streams, drainage network and pond Rock samples of dark grey shale were collected to determine if the surface rock were the source of the arsenic contamination. In addition in situ water quality parameters were recorded at all the sampling sites using the YSI 650 Sonde unit. Water parameters tested were temperature, conductivity, total dissolved solids, pH, NH4, N03, chloride and turbidity. All water and sediment samples collected were dispatched to an accredited chemical laboratory in Kuching for analysis of arsenic. The findings show arsenic is found in all the ponds and drain ranges from 10 to 120 Ilgll in water and 10.6 to 60.8 ppm in sediment samples respectively. One of the three rivers show elevated arsenic in both water and sediment samples with readings 10 Ilgll and 34.7 ppm for water and sediment samples respectively. The rest of the rivers recorded negligible arsenic readings. The rock samples returned with assays results ranging from 7.6 - 299.9 ppm. Meanwhile the in situ tests show no extreme readings. The results of the water and sediment analysis demonstrated that arsenic is occurring at varying concentration at each type of water bodies. The study identified the exposed shale outcrops are the source of the arsenic contamination.